Exosomes From M2 Macrophage Promote Peritendinous Fibrosis Posterior Tendon Injury via the MiR-15b-5p/FGF-1/7/9 Pathway by Delivery of circRNA-Ep400 - Yu, Yinxian; Sun, Binbin; Wang, Zhuoying; Yang, Mengkai; Cui, Zhi; Lin, Subin; Jin, Mingming; Yi, Chengqing (Frontiers in Cell and Developmental Biology, 2021)
Achilles tendon rupture prognosis is usually unsatisfactory. After the tendon is injured, it may not function properly because of the fibrotic healing response, which restrains tendon motion. Inflammatory monocytes and tissue-resident macrophages are indispensable regulators in tissue repair, fibrosis, and regeneration. Exosomes from macrophages are crucial factors in tissue microenvironment regulation following tissue injury. This study therefore aimed to clarify the roles of macrophage exosomes in tendon injury (TI) repair. The results show that macrophages play a role after TI. M1 macrophages were increased relative to peritendinous fibrosis after TI. High-throughput sequencing showed abnormal expression of circRNA between exosomes from M2 and M0 macrophages. Among the abnormal expressions of circRNA, circRNA-Ep400 was significantly increased in M2 macrophage exosomes. The results also show that M2 macrophage-derived circRNA-Ep400-containing exosomes are important for promoting peritendinous fibrosis after TI. Bioinformatics and dual-luciferase reporting experiments confirmed that miR-15b-5p and fibroblast growth factor (FGF)-1/7/9 were downstream targets of circRNA-Ep400. High circRNA-Ep400-containing exosome treatment inhibited miR-15b-5p, but promoted FGF1/7/9 expression in both fibroblasts and tenocytes. Furthermore, high circRNA-Ep400-containing exosome treatment promoted fibrosis, proliferation, and migration in both fibroblasts and tenocytes. Taken together, the results show that M2 macrophage-derived circRNA-Ep400-containing exosomes promote peritendinous fibrosis after TI via the miR-15b-5p/FGF-1/7/9 pathway, which suggests novel therapeutics for tendon injury treatment.